2016
DOI: 10.1016/j.cej.2015.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozonation of swimming pool water on formation of volatile disinfection by-products – A laboratory study

Abstract: Ozonation experiments were performed using unchlorinated tap water used for filling municipal swimming pools, actual pool water and pool water polluted by addition of fresh tap water and artificial body fluid to evaluate ozone kinetics and water quality effects on formation of volatile disinfection byproducts during subsequent chlorination. The ozone reaction was observed to behave according to first order kinetics. For tap water half-life was 4 min whilst polluted and unpolluted pool water exhibited half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
(31 reference statements)
5
27
1
Order By: Relevance
“…The radical oxidation of that fraction of DOC enhances its reactivity to chlorine, and consequently the formation of TCM. The decrease in the concentration of TCM with a fourth and fifth dose is due to mineralization of that fraction of DOC with increasing oxidation [14]. Cheema et al [19] observed a similar trend in the formation of THMs with different doses of O 3 , as reported by Hansen et al [14] (Table A3).…”
Section: Effect On Thmssupporting
confidence: 71%
See 4 more Smart Citations
“…The radical oxidation of that fraction of DOC enhances its reactivity to chlorine, and consequently the formation of TCM. The decrease in the concentration of TCM with a fourth and fifth dose is due to mineralization of that fraction of DOC with increasing oxidation [14]. Cheema et al [19] observed a similar trend in the formation of THMs with different doses of O 3 , as reported by Hansen et al [14] (Table A3).…”
Section: Effect On Thmssupporting
confidence: 71%
“…In the study of different doses of O 3 in clean pool water (TOC 1.5 mg·L −1 ) , the formation of TCM increased from 25 to 60 µg·L −1 with the first three subsequent doses (2 mg·L −1 of O 3 each) and then with further addition decreased to 45 µg·L −1 , but still remained higher compared with chlorination (25 µg·L −1 ) [14] (Table A3) The increase in the formation of TCM with initial dose of O 3 in the clean pool water is likely due to decomposition of O 3 to OH • and radical oxidation of fraction of DOC present in the pool water, which has low reactivity towards chlorine. The radical oxidation of that fraction of DOC enhances its reactivity to chlorine, and consequently the formation of TCM.…”
Section: Effect On Thmsmentioning
confidence: 99%
See 3 more Smart Citations